Potensi Herbal Indonesia sebagai Pengurang Mual Muntah pada Kehamilan: Scoping Review: Potential of Indonesian Herbs as Reducing Nausea Vomiting in Pregnancy: Scoping Review - Pratiwi, Tan Mike; Noviyati Rahardjo Putri (Indonesian Journal of Midwifery (IJM), 2024)
As many as 50 - 80% of pregnant women experience nausea and vomiting as a result of hormonal changes during pregnancy. Nausea and vomiting can affect psychosocial conditions and affect the life functions of pregnant women such as fatigue, lack of energy, lack of interest and pleasure, irritability, lack of preparation for childbirth, reduce work productivity, reduce quality of child care, reduce quality of life and increase anxiety. On the other side, the abundance of herbal plants available in Indonesia has the potential to overcome nausea and vomiting in pregnancy. This study aims to analyze various scientific literacy related to herbal plants in Indonesia that can be given to reduce nausea and vomiting in pregnancy. This research method is a scoping review. Data is accessed from various database sources; Google Scholar, PubMed, Science Direct in the period 2013 to 2023. The main topic search keywords are; herbal, aromatherapy, nausea and vomiting in pregnancy. The results of this study concluded that herbal plants available in Indonesia have potential as non-pharmacological drugs to treat nausea and vomiting. Herbs that have been proven effective in reducing nausea and vomiting are ginger (Zingiber officinale), lemon (Citrus Lemon), lavender (Lavandula angustifolia), and mint (Mentha Piperita).   Abstrak Sebanyak 50 - 80% ibu hamil mengalami mual dan muntah akibat perubahan hormonal selama kehamilan. Mual dan muntah dapat mempengaruhi kondisi psikososial dan mempengaruhi fungsi hidup ibu hamil seperti kelelahan, kurang tenaga, kurang minat dan kesenangan, mudah tersinggung, kurang persiapan persalinan, menurunkan produktivitas kerja, menurunkan kualitas pengasuhan anak, menurunkan kualitas pengasuhan. hidup dan meningkatkan kecemasan. Di sisi lain, banyaknya tanaman herbal yang tersedia di Indonesia berpotensi untuk mengatasi mual muntah pada kehamilan. Penelitian ini bertujuan untuk menganalisis berbagai literasi ilmiah terkait tumbuhan herbal di Indonesia yang dapat diberikan untuk mengurangi mual muntah pada kehamilan. Metode penelitian ini adalah scoping review. Data diakses dari berbagai sumber database; Google Scholar, PubMed, Science Direct pada periode 2013 hingga 2023. Kata kunci pencarian topik utama adalah; herbal, aromaterapi, mual dan muntah pada kehamilan. Hasil penelitian ini menyimpulkan bahwa tanaman herbal yang tersedia di Indonesia berpotensi sebagai obat nonfarmakologi untuk mengatasi mual muntah. Herbal yang telah terbukti efektif untuk mengurangi rasa mual dan muntah adalah jahe (Zingiber officinale), lemon (Citrus Lemon), lavender (Lavandula angustifolia), dan mint (Mentha Piperita).